Relationship Between Patient‐Reported Swelling and Magnetic Resonance Imaging–Defined Effusion‐Synovitis in Patients With Meniscus Tears and Knee Osteoarthritis. Issue 3 (28th February 2019) - MacFarlane, Lindsey A.; Yang, Heidi; Collins, Jamie E.; Guermazi, Ali; Mandl, Lisa A.; Levy, Bruce A.; Marx, Robert G.; Safran‐Norton, Clare E.; Losina, Elena; Katz, Jeffrey N.; ,
Abstract : Objective: Synovitis is a prevalent feature in patients with knee osteoarthritis (OA) and meniscal tear and is associated with pain and cartilage damage. Patient‐reported swelling is also prevalent in this population. The aim of this study was to investigate the cross‐sectional association between patient‐reported swelling and effusion‐synovitis detected by magnetic resonance imaging (MRI) in patients with OA and meniscal tear. Methods: We used baseline data from a multicenter, randomized controlled trial, Meniscal Tear in Osteoarthritis Research (METEOR). MRI‐identified effusion‐synovitis, a proxy for effusion and synovitis on noncontrast MRIs, was graded as none/small versus medium/large. Using MRI‐identified effusion‐synovitis as the gold standard, we assessed the sensitivity, specificity, and positive predictive value of patient self‐reported swelling in the previous week (none, intermittent, constant) to detect effusion and synovitis. Results: We analyzed data from 276 patients. Twenty‐five percent of patients reported no swelling, 40% had intermittent swelling, and 36% had constant swelling. Fifty‐two percent had MRI‐identified medium/large–grade effusion‐synovitis. As compared with MRI‐identified effusion‐synovitis, any patient‐reported swelling (versus none) had a sensitivity of 84% (95% confidence interval [95% CI] 77–89), a specificity of 34% (95% CI 26–43), and a positive predictive value of 57% (95% CI 54–61). A history of constant swelling (versus none or intermittent) showed a sensitivity of 46% (95% CI 37–54), a specificity of 75% (95% CI 67–82), and a positive predictive value of 66% (95% CI 58–74). Conclusion: We found that the sensitivity and specificity of patient‐reported swelling were modest when compared with effusion‐synovitis detected by MRI. These data urge caution against using patient‐reported swelling as a proxy of inflammation manifesting as effusion‐synovitis.